Mechanically Powered Motion Imaging Phantoms: Proof of Concept - Gomez, Alberto; Schmitz, Cornelia; Henningsson, Markus; Housden, James; Noh, Yohan; Zimmer, Veronika A.; Clough, James R.; Oksuz, Ilkay; Toussaint, Nicolas; King, Andrew P.; Schnabel, Julia A. (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2019)
Motion imaging phantoms are expensive, bulky and difficult to transport and set-up. The purpose of this paper is to demonstrate a simple approach to the design of multi-modality motion imaging phantoms that use mechanically stored energy to produce motion.We propose two phantom designs that use mainsprings and elastic bands to store energy. A rectangular piece was attached to an axle at the end of the transmission chain of each phantom, and underwent a rotary motion upon release of the mechanical motor. The phantoms were imaged with MRI and US, and the image sequences were embedded in a 1D non linear manifold (Laplacian Eigenmap) and the spectrogram of the embedding was used to derive the angular velocity over time. The derived velocities were consistent and reproducible within a small error. The proposed motion phantom concept showed great potential for the construction of simple and affordable motion phantoms.
CRIS-Team Scopus Importer:2023-03-08